DEVELOPMENT OF PEDAGOGICAL TECHNOLOGY OF PROGNOSTIC COMPETENCE FORMATION IN FUTURE COMPUTER SCIENCE BACHELORS - Прошкин, Владимир; Шаравара, Виктор (SWorldJournal, 2021)
The author’s interpretation of pedagogical technology of prognostic competence formation of future computer sciences bachelors is given in the article. Pedagogical technology is presented as four interconnected blocks: target, theoretical and methodologi